1997
DOI: 10.1007/978-3-540-69648-3_22
|View full text |Cite
|
Sign up to set email alerts
|

The Epoch of Major Star Formation in High-z Quasar Hosts

Abstract: Abstract. We present the results of our observing program on NIR spectroscopy of high-redshift (z) quasars which have been undertaken both at Kitt Peak National Observatory and at Mauna Kea Observatory, University of Hawaii. These data are utilized for studying the epoch of major star formation in high-z quasar hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
1999
1999

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Lípari et al 1993), such extreme Fe II emitters appear to be rare in the low-z universe. Recently, we obtained NIR spectra of two radio-loud, flat-spectrum, high-z quasars (B 1422+231 at z = 3.6 and PKS 1937−101 at z = 3.8) and found that their flux ratios of F (Fe II λλ4434-4684)/F (Hβ) are much less than those of the other high-z quasars (Kawara et al 1996;Taniguchi et al 1996Taniguchi et al , 1997, and in fact are similar to those of radio-loud, flat-spectrum, low-z quasars with normal optical Fe II emission. These new observations suggest that high-z quasars may exhibit a range of values of F (Fe II λλ4434-4684)/F (Hβ) similar to what has been observed for low-z quasars.…”
Section: Lbqs Compositementioning
confidence: 99%
“…Lípari et al 1993), such extreme Fe II emitters appear to be rare in the low-z universe. Recently, we obtained NIR spectra of two radio-loud, flat-spectrum, high-z quasars (B 1422+231 at z = 3.6 and PKS 1937−101 at z = 3.8) and found that their flux ratios of F (Fe II λλ4434-4684)/F (Hβ) are much less than those of the other high-z quasars (Kawara et al 1996;Taniguchi et al 1996Taniguchi et al , 1997, and in fact are similar to those of radio-loud, flat-spectrum, low-z quasars with normal optical Fe II emission. These new observations suggest that high-z quasars may exhibit a range of values of F (Fe II λλ4434-4684)/F (Hβ) similar to what has been observed for low-z quasars.…”
Section: Lbqs Compositementioning
confidence: 99%